Development of the World Federation of Hemophilia Shared Decision‐Making Tool - Coffin, Donna; Skinner, Mark W.; Thornburg, Courtney D.; Hayes, Brendan K.; Sannié, Thomas; Kaeser, Gwendolyn E.; Chadwick, Julia; Naccache, Mayss; Pierce, Glenn F. (Haemophilia : the official journal of the World Federation of Hemophilia, 2024)
Introduction The use of shared decision‐making (SDM) in clinical settings is becoming more prevalent. The evolving and increasingly complex treatment landscape of haemophilia management has augmented the need and desire for SDM between patients and their healthcare team. SDM tools have been used in other chronic conditions and can be an effective form of education for patients and clinicians. Aim The World Federation of Hemophilia (WFH) partnered with people with haemophilia (PWH), patient advocacy groups, and healthcare practitioners to form an expert working group to develop an educational tool for PWH and their caregivers. The primary objectives included educating PWH on the available prophylactic treatments and facilitating discussion between PWH and their healthcare team. Methods The tool was proposed and developed by the expert working group, workshopped at conference round tables, and evaluated in two focus groups. Results The interactive WFH SDM Tool guides users through the SDM treatment journey and provides an opportunity for reflection on current disease impact and treatment preferences, educational fact sheets and videos, and a comparison between treatment classes. Two forms of the SDM Tool are available: an online platform with a summary page that may be printed and shared and a printable workbook. All evidence in the tool is based on the prescribing information or phase III clinical trial publications. The Tool will be updated twice each year. Conclusion The WFH SDM Tool is the first available resource that translates published guidance on SDM in haemophilia into a practical, user‐friendly tool aimed at facilitating patient‐centred treatment decisions.